Editorial Special section on ecological restoration of ecosystems - Méndez-Toribio, Moisés; Gómez-Ruíz, Pilar A. (Instituto de Ecología, A.C., 2022)
The issues addressed in this special section are of great interest to a large number of restoration practitioners, ecologists, and decision makers in charge of financing and incentivizing ecological restoration actions. The generation of innovative knowledge together with its application is essential for the advancement and progress of restoration interventions and of this scientific discipline in Mexico and Latin America. The expectation is that the discussion around the issues addressed in this special section (and other relevant ones) will allow us to investigate the research areas that should be promoted in the medium and long term in our country.